The Actin Regulators Involved in the Function and Related Diseases of Lymphocytes - Sun, Jianxuan; Zhong, Xingyu; Fu, Xiaoyu; Miller, Heather; Lee, Pamela; Yu, Bing; Liu, Chaohong (Frontiers in Immunology, 2022)
Actin is an important cytoskeletal protein involved in signal transduction, cell structure and motility. Actin regulators include actin-monomer-binding proteins, Wiskott-Aldrich syndrome (WAS) family of proteins, nucleation proteins, actin filament polymerases and severing proteins. This group of proteins regulate the dynamic changes in actin assembly/disassembly, thus playing an important role in cell motility, intracellular transport, cell division and other basic cellular activities. Lymphocytes are important components of the human immune system, consisting of T-lymphocytes (T cells), B-lymphocytes (B cells) and natural killer cells (NK cells). Lymphocytes are indispensable for both innate and adaptive immunity and cannot function normally without various actin regulators. In this review, we first briefly introduce the structure and fundamental functions of a variety of well-known and newly discovered actin regulators, then we highlight the role of actin regulators in T cell, B cell and NK cell, and finally provide a landscape of various diseases associated with them. This review provides new directions in exploring actin regulators and promotes more precise and effective treatments for related diseases.